INSTRUCTIONAL MEDIA AND MANAGEMENT OF ELEMENTARY SCHOOLS EDUCATION IN KWARA STATE, NIGERIA - Abdullahi Nimota Jibola Kadir (The University of Kuningan, 2020)
ABSTRACT Instructional media within the educational institutions could bring the world into the classroom and enhance effective management of education. This study examined the relationship between projected media, non-projected visual, simulation and games and management of elementary education in public primary schools in Kwara State, Nigeria. Stratified random sampling technique was used to select 306 head teachers from a population of 1, 406 and 384 teachers from a population of 14,206 in public primary schools in Kwara State with the use of Research Advisor (2006) table of determining sample size of a known population. Data was collected using Instructional Media and Management of Elementary Education Questionnaire (IMMEEQ). The data was analysed using descriptive statistics and t-test statistical analysis. The results showed that there were significant and positive relationship between projected media, non-projected visual, simulation and games and management of elementary education. Based on the findings it was therefore recommended that government and head teachers should provide appropriate projected media for teachers to disseminate information to learners in the classroom. Also, head teachers should continue to encourage teachers to make use of non-projected visual to arouse the interest and gain the attentions of the learners in order to aid the teachers’ explanations and make learning of subject matter understandable to learners during teaching and learning process. Furthermore, teachers should also make use of simulation and games to enhance effective learners’ performance in learning in order to realize effective management of elementary schools’ education in Nigeria. Keywords: instructional media, motivation, projected media, elementary education, organising